Facing paradoxical identities: How Indonesian organic food community unify consumers and environmentalist identities - Estu Putri Wilujeng (Universitas Trunojoyo Madura, 2021)
This article explored how the Indonesian organic food community builds its identity as both consumers and environmentalists, which is often thought to be a paradox. Some researchers argue that combining consumption and environmental preservation under green consumption is a challenge and an oxymoron. Nevertheless, the organic food community is still able to build their identities. The author argued that organic communities have transformed into space to empower and shape those identities using conventional and new media as part of green political consumerism. To understand this issue, the author used qualitative research by collecting the communities’ official documents, webpage, and social media accounts’ posts. The author also interviewed the founders of two communities, Komunitas Organik Indonesia (KOI/ Indonesian Organic Community) and Lingkar Organik (LO/ Organic Circle), a KOI member. The author did participatory observation in one of KOI’s WhatsApp Groups for their members. Then, the author triangulated the data and analyzed it. The results revealed that communities maintain and transform their green value into identities and real action by conditioning their members with community structures, activities, and access to organic food either through online or offline services. Therefore, having both identities is not a paradox.